Assessing time-dependent damage to a cable-stayed bridge through multi-directional ground motions based on material strain measures. (15th January 2021) - Li, Xiaozhen; Fu, Peiyao; Xu, Lueqin; Xin, Lifeng
Highlights: The degradation characteristics of RC materials under atmospheric exposure are considered. The time-dependent FE models of an in-service cable-stayed bridge are established. The most damaging seismic input mode is discussed. The damage evaluation index for the cable-stayed bridge are determined. The time-dependent seismic damage to the bridge under the considered input is evaluated. Abstract: Investigations into previous earthquakes indicated that the seismic damage to bridges was closely related to the length of their service lives. Based on this observation, finite-element time-dependent models of a cable-stayed bridge with a single pylon and wide deck were established by considering the effects of concrete carbonization on various structural components. Ground motion records were selected and matched with the design spectrum of site classification Ⅰ. Different combinations methods of ground motions inputs were compared with respect to the strain distributions of critical elements, and the representative method was then determined according to the maximum responses. The strain limits of reinforcing steel and concrete were defined based on previous studies, and were used to identify the time-dependent damage states of critical elements under earthquakes. The incremental dynamic analysis (IDA) method was applied to comparatively investigate the effect of concrete carbonization on the seismic response of cable-stayed bridge. Using the defined strain limits, the effect of concrete carbonization on the time-dependent seismic damage to the cable-stayed bridge was also discussed. The results show that the strength of steel and concrete can decrease as much as 23.30% and 12.66% respectively due to the concrete carbonization. The coupling damage to the bridge is found under multi-directional ground motions. The pylon is the most critical element during three-way seismic waves, in which the base suffers the most serious damage, the deck-level section follows and the cable anchorage portion remains in slight damage state. Taking the concrete carbonization into consideration, the damage level of the pylon base increases significantly, and brittle failure may occur to the pylon base when subjected to earthquakes with high peak ground accelerations (PGAs). However, the damage levels of other critical portions of the pylon decrease when the concrete carbonization is considered.